2011
DOI: 10.4028/www.scientific.net/amm.52-54.488
|View full text |Cite
|
Sign up to set email alerts
|

Porous NiO-SDC Carbonates Composite Anode for LT-SOFC Applications Produced by Pressureless Sintering

Abstract: Composite anodes made of NiO and SDC-(Li/Na)2CO3 were investigated in relation to their structure, morphology, and porosity. As a first step, the anode powder was prepared by mixing the NiO with SDC-(Li/Na)2CO3 via solid state reaction in weight percentage of 60 : 40 wt% and in various compositions of carbonates (20 and 30wt%), namely NiO-SDC8020 and NiO-SDC7030, respectively. The powder mixtures were then calcined at 680oC. The resultant powder was fine with surface area of about 13.10-13.70 m2/g and an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
4
8
0
Order By: Relevance
“…However, the crystallite size of SDCC decreased to 484.0 Å and maintained a cubic phase (lattice parameter a = 5.43319 Å). No remarkable secondary constituents were observed in the NiO-SDCC composite powder within the sensitivity of the XRD instrument, which is consistent with other studies [23,24]. Figure 3a shows the morphology of raw SDC powder, and Figure 3b shows the morphology of the SDCC composite powders after calcination.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, the crystallite size of SDCC decreased to 484.0 Å and maintained a cubic phase (lattice parameter a = 5.43319 Å). No remarkable secondary constituents were observed in the NiO-SDCC composite powder within the sensitivity of the XRD instrument, which is consistent with other studies [23,24]. Figure 3a shows the morphology of raw SDC powder, and Figure 3b shows the morphology of the SDCC composite powders after calcination.…”
Section: Resultssupporting
confidence: 78%
“…This morphology led to the increment of the NiO-SDCC surface area by 27.82 m 2 •g -1 , compared with the surface area value in a previous study [23]. The increase in surface area is necessary to improve the gas diffusion channels in the anode and, consequently, to enlarge the TPB density of the anode [9,26].…”
Section: Resultsmentioning
confidence: 95%
“…Meanwhile, the crystallite size of SDC is slightly larger compared to NiO because of the carbonate coating on SDC particle. This trend is also consistent with previous studies reported by Jarot et al [17] and Ma et al [20]. The larger crystallite size of Ag as compared to NiO and SDC might be resulted from larger particle size of starting material (300 to 700 nm) Fig.…”
Section: Sample Characterisationsupporting
confidence: 92%
“…Materials and sample preparation SDC powder (Kceracell, Korea) and (Li 0.67 Na 0.33 ) CO 3 (Sigma Aldrich, USA) at the weight ratio of 4:1 were ball-milled in ethanol for 24 h, oven dried, and subsequently calcined at 680°C at a rate of 5°C•min -1 for 1 h in air to acquire SDCC electrolyte [18,21]. The NiO powder (Kceracell, Korea) and aforementioned SDCC powder were ball-milled at different weight ratios (50 -70 wt.…”
Section: Methodsmentioning
confidence: 99%
“…NiO-samarium-doped ceria carbonate (NiO-SDCC) has been explored for its excellent compatibility as LT anode with other SOFC components [18][19][20]. Jarot et al [21] reported on the feasibility of NiO-SDCC as composite anode with the NiO loading of 60 wt. % and subsequently pre-calcined at 680°C.…”
Section: Introductionmentioning
confidence: 99%